Dry Emulsions based on Alpha Cyclodextrin and Vegetable Oils for Buccal Delivery of Lipophilic Drugs - Abruzzo, Angela; Saladini, Bruno; Dalena, Francesco; Nicoletta, Fiore P.; Luppi, Barbara; Bigucci, Federica; Cerchiara, Teresa (Drug Delivery Letters, 2020)
Background: Buccal delivery of drugs can be used as an alternative administration route to conventional oral route avoiding the liver first-pass effect and improving patient compliance. Objective: The goal of this work was to develop dry emulsions for buccal delivery of ketoprofen, used as a lipophilic model drug. The influence of two vegetable oils, olive oil or wheat germ oil, in the presence of α-cyclodextrin and different drying techniques on the dry emulsion properties was evaluated. Methods: Emulsions were prepared by adding olive oil or wheat germ oil to an aqueous solution of α-cyclodextrin and subsequently dried through an oven, freeze-dryer or spray-dryer. Dry emulsions were characterized in terms of yield, encapsulation efficiency, morphology and drug solid-state. In vitro drug release and permeation studies were carried out to evaluate dry emulsion ability to release the drug and to allow its permeation through the esophageal porcine epithelium. Results: The formation of stable and milky emulsion was assured by cyclodextrin ability to interact with oil components obtaining an inclusion complex with amphiphilic property able to act as a surfaceactive agent. The drying process influenced the yield and the encapsulation efficiency, while no significant differences were observed between olive oil and wheat germ oil. Freeze-dried emulsions, selected as the best formulations, resulted in fast release of drug thereby ensuring its permeation across the epithelium. Conclusion: Dry emulsions prepared with a simple and easy method, using natural ingredients and avoiding synthetic surfactants and organic solvents, could be used for buccal delivery of lipophilic drugs.
Keywords: Ketoprofen